2020
DOI: 10.1016/j.abb.2020.108517
|View full text |Cite
|
Sign up to set email alerts
|

Conformation-dependent membrane permeabilization by neurotoxic PrP oligomers: The role of the H2H3 oligomerization domain

Abstract: The relationship between prion propagation and the generation of neurotoxic species and clinical onset remains unclear. Several converging lines of evidence suggest that interactions with lipids promote various precursors to form aggregation-prone states that are involved in amyloid fibrils. Here, we compared the cytotoxicities of different soluble isolated oligomeric constructs from murine full-length PrP and from the restricted helical H2H3 domain with their effects on lipid vesicles. The helical H2H3 domain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 78 publications
0
1
0
Order By: Relevance
“…Recently, Huin et al, evaluated the viability of differentiated cerebellar granule cells lacking PrPC, exposed to PrP oligomers. Again, the authors observed a significant rate of neuronal death associated with the ability of the oligomers to permeabilize membranes [ 130 ].…”
Section: Functional Commonalitiesmentioning
confidence: 99%
“…Recently, Huin et al, evaluated the viability of differentiated cerebellar granule cells lacking PrPC, exposed to PrP oligomers. Again, the authors observed a significant rate of neuronal death associated with the ability of the oligomers to permeabilize membranes [ 130 ].…”
Section: Functional Commonalitiesmentioning
confidence: 99%